Using magnetic techniques to calibrate hydrocarbon migration in petroleum systems modelling: A Case Study from the Lower Tertiary, UK Central North Sea - Badejo,SA; Muxworthy,AR; Fraser,A; Neumaier,M; Perkins,JR; Stevenson,GR; Davey,R (Geophysical Journal International, 2021)
Magnetic minerals form or alter in the presence of hydrocarbons, making them a potential magnetic proxy for identifying hydrocarbon migration pathways. In this paper, we test this idea by magnetically measuring core samples from the Tay Fan in the Western Central Graben in the Central North Sea. In a companion paper, 3-D petroleum systems modelling has been carried out to forward model migration pathways within the Tay Fan. Rock magnetic experiments identified a range of magnetite, maghemite, iron sulphides, siderite, goethite and titanohematite, some of which are part of the background signal, and some due to the presence of hydrocarbons. Typical concentrations of the magnetic minerals were ∼10–200 ppm. Importantly, we have identified an increasing presence of authigenic iron sulphides (likely pyrite and greigite) along the identified lateral hydrocarbon migration pathway (east to west). This is likely caused by biodegradation resulting in the precipitation of iron sulphides, however, though less likely, it could alternatively be caused by mature oil generation, which subsequently travelled with the migrating oil to the traps in the west. These observations suggest mineral magnetic techniques could be a rapid alternative method for identifying the severity of biodegradation or oil maturity in core sample, which can then be used to calibrate petroleum systems models.